Effect of Two Remineralizing Agents on Dentin Microhardness of Non-Caries Lesions - Haleh Heshmat; Haleh Kazemi Yazdi; Maryam Hoorizad Ganjkar; Farhad Chaboki; Mahoor Shokri; Mohamad Javad Kharazifard (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: The prevalence of non-carious dentin lesions is on the rise mainly due to improved life expectancy. Successful management of these lesions is often challenging, and given that dentin can be remineralized, adverse consequences due to progression of these lesions can be prevented or minimized as such.Purpose: This study aimed to assess the effect of casein phosphopeptide amorphous calcium phosphate (CPP-ACP) and Remin-Pro remineralizing agents on dentin microhardness of non-carious dentin lesions.Materials and Method: This in vitro, experimental study evaluated 36 extracted sound human premolars. The teeth were decoronated at the cementoenamel junction. Enamel was removed, and dentin was exposed at the cervical third of the buccal surface. The primary microhardness of dentin was then measured. The teeth, standardized in terms of dentin microhardness, then underwent demineralization by acid etching and were subjected to microhardness test again. They were then randomized into three groups for treatment with CPP-ACP, Remin-Pro, and artificial saliva (control), and dentin microhardness was measured for the third time after treatment. Data were analyzed using ANOVA.Results: Within group comparisons showed a significant difference in microhardness at the three time points in all three groups (p< 0.005). Between-group comparisons revealed that the microhardness of the three groups was not significantly different at baseline or after demineralization. However, the microhardness of the three groups was significantly different after the intervention (p= 0.000). Pairwise comparisons revealed significantly higher microhardness in the CPP-ACP group than the other two groups (p= 0.003). Remin-Pro and the control groups were not significantly different in this respect (p= 0.340).Conclusion: CPP-ACP can be used for remineralization of non-caries dentin lesions; however, Remin-Pro does not appear to be effective for this purpose.